2022
DOI: 10.3389/fmed.2022.1020648
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic removal of a massive trichobezoar in a pediatric patient by using a variceal ligator cap: A case report and literature review

Abstract: A trichobezoar is commonly formed in the gastrointestinal tract by ingestion of an individual’s own hair. A trichobezoar formed by hair and artificial materials constitutes a rare etiology scarcely reported in the current literature. A mixture with hair-like synthetic fibers not only increases the risk for trichobezoar formation but also makes it more difficult for endoscopic removal. Herein, we report on a case in which a trichobezoar, caused by the consumption of human hair and synthetic yarn, was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
9
2
Order By: Relevance
“…Hair and food residues were entangled with the hair, resulting in reduced electrical conductivity. Since the report by Gorter et al and Lu et al, there have been reports of endoscopic removal of trichobezoars 2,3 . However, all of these were smaller in size than that in the present case, 2,3 suggesting that they were easier to grasp with snare and forceps 5,6 .…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Hair and food residues were entangled with the hair, resulting in reduced electrical conductivity. Since the report by Gorter et al and Lu et al, there have been reports of endoscopic removal of trichobezoars 2,3 . However, all of these were smaller in size than that in the present case, 2,3 suggesting that they were easier to grasp with snare and forceps 5,6 .…”
Section: Discussioncontrasting
confidence: 45%
“…However, all of these were smaller in size than that in the present case, 2,3 suggesting that they were easier to grasp with snare and forceps 5,6 . Lu et al indicated that successful endoscopic removal could depend on the size and morphology of bezoars 3 . The removal of large trichobezoars appears to be difficult with an endoscopic procedure only.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Retrieval may need multiple endoscopic passes and a prolonged procedure time of up to 5 hrs. We have summarized case reports (Table 2) that have described the successful removal of trichobezoar endoscopically (14–23). These case reports are, however, outnumbered by cases reported where endoscopic removal was unsuccessful.…”
Section: Discussionmentioning
confidence: 99%